ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PADA PT. BLUE BIRD TBK - Ani Rakhmanita; Desy Tri Anggarini (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
This study aimed to analyze the financial performance of PT. Blue Bird Tbk, based Ratios Liquidity, Solvency, Activity and Profitability in 2014 until 2016. This study used quantitative descriptive approach. The results showed that: (1) The liquidity ratio to measure the ability of PT Blue Bird Tbk in meeting short-term obligations through indicators Current Ratio and Cash Ratio is in the category of performance